Ensuring human information rights in social networks - Tokareva, Ksenia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
In the light of globalization processes, issues related to information security and protection are becoming more and more relevant. Information technologies are developing faster than the legal regulation of various information resources. The problem of determining specific informational rights in social networks and the ways of ensuring them require innovative approaches, taking into account the peculiarities of the functioning of such networks and the process of carrying out communications within them. Ensuring human and citizen rights on the Internet has become the newest indicator of a democratic state, so this issue remains open for further research. The purpose of the article is to research directions for ensuring human information rights in social networks at the current stage of information society development. It has been established that information has become a factor in the stable development of a society that receives, uses and distributes information. On the basis of the analysis of modern opinions of scientists, informational rights that require separate approaches to provision in social networks are singled out. Among them: the right to freedom of expression of views, thoughts and speech, as well as free use and dissemination of information; the right to protection of personal information, as well as to know during the period of information collection (before the start of its use), what information about a person and for what purpose is collected, how, by whom and for what purpose it is used, transferred or distributed; the right to an information space free from materials that pose a threat to the physical, intellectual, moral and psychological state of a person and others. It is emphasized that the provision of human informational rights in social networks should be carried out at the legislative level, taking into account the technical features of the functioning of information and communication technologies. The main directions of provision include: establishment of enhanced standards of technical and legal protection of personal data, expansion of the responsibilities of social network owners in the field of data security, establishment of responsibility for violations of established requirements, expansion of ways to protect intellectual property rights on the Internet and introduction of strict filtering restrictions information space in social networks for certain groups of people.